Elite Capture Through Information Distortion: A Theoretical Essay - Jean-Philippe Platteau; Vincent Somville; Zaki Wahhaj (University of Kent, School of Economics, 2013)
We investigate donor-beneficiary relationships in participatory development programs, where (i) communities are heterogeneous and dominated by the local elite, (ii) the elite strategically propose a project to the donor, knowing that the latter has imperfect knowledge of the needs of the target population. We analyze how changes in the donor's outside option or information about the needs of the target population affect elite capture. Our central, paradoxical result is that a more attractive outside option, or a higher quality of donor's information may end up encouraging the local elite to propose a project that better matches their own preference rather than the preference of the grassroots. Moreover, in the case where the noise in the donor's information follows a normal distribution, we find that a better outside option generally decreases elite capture but improved information about the needs of the target population is likely to increase elite capture.
Keywords: O12; O21; 330; community-driven development; aid effectiveness; elite capture; preference targeting; information distortion